Expresso exchange – series 1 / Nor Adila Zulkifli ... [et al.] - Zulkifl, Nor Adila; Mohd Halimi, Hazureen; Tumiran, Mad Sapri; Alias, Rosmaliah; Zulkifli, Siti Zaidathul Iman; Bachtiar, Nurin Irdina Jamsari (Faculty of Pharmacy, 2025)
The purposes of this program were to provide postgraduate students with exposure to practical approaches in pharmacy research, encourage academic interactions between students and lecturers, and create a knowledge-sharing platform in a relaxed atmosphere. The objectives of the program were to enhance understanding of current research strategies and promote two ways academic interactions between students and lecturers.